New chromosomal evidence for the origin of Triatoma infestans populations from Brazil - Pereira, N. P. [UNESP]; Alevi, K. C. C. [UNESP]; Rosa, J. A. [UNESP]; Azeredo-Oliveira, M. T. V. [UNESP] (Funpec-editora, 2016)
In this study, the karyometry of different Triatoma infestans populations from different states of Brazil was analyzed and compared with those of a population from Cochabamba. No significant differences were found between the population from Cochabamba and those from Brazil. These results are consistent with the origin of the T. infestans populations of Brazil by a founder effect from Cochabamba. Moreover, these findings also confirm that a founder effect occurred during the dispersal of T. infestans populations in different Brazilian states.
Keywords: Chromosome measurement; Founder effect; Karyometry; Chagas disease